2011
DOI: 10.3141/2227-04
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation and Cost-Effectiveness of Saw and Seal Method to Control Reflection Cracking in Composite Pavements

Abstract: The Louisiana Department of Transportation and Development has tested various techniques and treatments to control reflection cracking in composite pavements since the 1970s. However, the performance and cost-effectiveness of these methods have not been consistently evaluated. The objective of this study was to evaluate the performance of hot-mix asphalt (HMA) overlays of portland cement concrete pavement sections built with the saw and seal method across the state and to assess the cost-effectiveness of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…This suggests that saw and seal treatment used in the preservation asphalt overlay is effective to control reflection cracking. The similar finding was reported by Elseifi et al ( 27 ).…”
Section: Resultssupporting
confidence: 92%
“…This suggests that saw and seal treatment used in the preservation asphalt overlay is effective to control reflection cracking. The similar finding was reported by Elseifi et al ( 27 ).…”
Section: Resultssupporting
confidence: 92%
“…Saw cuts made in the HMA overlay were both transverse and longitudinal. The study found that the saw and seal method was an overall success in increasing the service life of the pavement [5]. Seven test sections indicated an increase in service life ranging from 4 to 12 years and six of the test sections indicated an increase in service life of 3 years, resulting in an expected average increase in service life of 4 years.…”
Section: Figurementioning
confidence: 94%
“…In Louisiana, the saw and seal method used on 15 composite pavements were evaluated for their cost-effectiveness and effectiveness in reducing reflective cracking [5]. The sections, monitored for a period of six or more years, experienced average annual daily traffic (AADT) ranging from 1,800 to 50,250, along with varying climate conditions.…”
Section: Figurementioning
confidence: 99%
“…Road segments were selected to represent different pavement conditions as described by the pavement condition index and with varying hot-mix asphalt thickness and base type. The pavement condition index varies from 95 to 100, 85 to 94, 65 to 84, 50 to 64, and 49 or less for very good, good, fair, poor, and very poor roads, respectively (12). Traffic volume widely varied in the selected sections, from an annual average daily traffic of 244 to 29,357; these traffic volumes ranged from low to heavy.…”
Section: Experimental Program Rwd Testingmentioning
confidence: 99%